2015
DOI: 10.1117/12.2084051
|View full text |Cite
|
Sign up to set email alerts
|

Autonomous color theme extraction from images using saliency

Abstract: Color theme (palette) is a collection of color swatches for representing or describing colors in a visual design or an image. Color palettes have broad applications such as serving as means in automatic/semi-automatic design of visual media, as measures in quantifying aesthetics of visual design, and as metrics in image retrieval, image enhancement, and color semantics. In this paper, we suggest an autonomous mechanism for extracting color palettes from an image. Our method is simple and fast, and it works on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…It rather argues achievements in identifying a novel application of color adjustment and developing a simple and concise solution that satisfies the needs of users without any user input. In terms of its methodological approach, an active engagement of human perception, particularly the perception of design‐experts, is yet been investigated fully despite recent studies have shown notable achievement in relation to color . It is expected that the full‐automation of our method largely reduces the tedious and time‐consuming tasks, which even well‐trained experts rarely evade.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It rather argues achievements in identifying a novel application of color adjustment and developing a simple and concise solution that satisfies the needs of users without any user input. In terms of its methodological approach, an active engagement of human perception, particularly the perception of design‐experts, is yet been investigated fully despite recent studies have shown notable achievement in relation to color . It is expected that the full‐automation of our method largely reduces the tedious and time‐consuming tasks, which even well‐trained experts rarely evade.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of its methodological approach, an active engagement of human perception, particularly the perception of design-experts, is yet been investigated fully despite recent studies have shown notable achievement in relation to color. 52,58,59 It is expected that the full-automation of our method largely reduces the tedious and time-consuming tasks, which even well-trained experts rarely evade.…”
Section: Technical Aspects To Be Improvedmentioning
confidence: 99%
“…This method tends to select various colors to span the different conspicuous colors in the three-dimensional (3D) scatter plot of the image pixels. 20 The colors extracted by this method may not be the most salient color in one cue in the 3D scatter plot.
Figure 9.Comparison with the saliency-based method proposed by Jahanian et al.
…”
Section: Experiments and Evaluationmentioning
confidence: 99%
“…
Figure 9.Comparison with the saliency-based method proposed by Jahanian et al. 20 The first color theme is extracted by Jahanian et al.’s method and the last is extracted by our model. (Color online only.
…”
Section: Experiments and Evaluationmentioning
confidence: 99%
“…Often colour palettes are generated by designers for practical application based on their knowledge of aesthetics with respect to either a design brief or the designer's own colour preferences . Colour palettes may be extracted automatically from an image or a set of images or even generated from a word . There are currently no established methods for predicting the visual similarity or visual difference between two colour palettes; the automated design systems that are being developed based on data and machine learning will require the ability to be able to predict similarity between colour palettes …”
Section: Introductionmentioning
confidence: 99%